Progressive accumulation of activated ERK2 within highly stable ORF45-containing nuclear complexes promotes lytic gammaherpesvirus infection. - Evonne N Woodson; Melissa S Anderson; Matthew S Loftus; Dean H Kedes (PLoS Pathogens, 2014)
De novo infection with the gammaherpesvirus Rhesus monkey rhadinovirus (RRV), a close homolog of the human oncogenic pathogen, Kaposi's sarcoma-associated herpesvirus (KSHV), led to persistent activation of the MEK/ERK pathway and increasing nuclear accumulation of pERK2 complexed with the RRV protein, ORF45 (R45) and cellular RSK. We have previously shown that both lytic gene expression and virion production are dependent on the activation of ERK [1]. Using confocal microscopy, sequential pull-down assays and FRET analyses, we have demonstrated that pERK2-R45-RSK2 complexes were restricted to the nucleus but that the activated ERK retained its ability to phosphorylate nuclear substrates throughout infection. Furthermore, even with pharmacologic inhibition of MEK beginning at 48 h p.i., pERK2 but not pERK1, remained elevated for at least 10 h, showing first order decay and a half-life of nearly 3 hours. Transfection of rhesus fibroblasts with R45 alone also led to the accumulation of nuclear pERK2 and addition of exogenous RSK augmented this effect. However, knock down of RSK during bona fide RRV infection had little to no effect on pERK2 accumulation or virion production. The cytoplasmic pools of pERK showed no co-localization with either RSK or R45 but activation of pERK downstream targets in this compartment was evident throughout infection. Together, these observations suggest a model in which R45 interacts with pERK2 to promote its nuclear accumulation, thereby promoting lytic viral gene expression while also preserving persistent and robust activation of both nuclear and cytoplasmic ERK targets.